Immigrants in the UK and in West Germany - Relative Income Position, Income Portfolio, and Redistribution Effects - Felix Büchel; Joachim R. Frick (Institute for the Study of Labor (IZA), 2003)
Based on data from the BHPS and the GSOEP, we analyse the economic performance of various ethnic groups in the UK and West Germany, as well as the effects of income redistribution on these populations. Taking the indigenous population of each country as the reference category, we find that, as a whole, the non-indigenous population in the UK fares much better than the immigrant population in Germany. However, the range of economic performance across different ethnic groups in the UK is much larger than that in Germany. The German corporatist welfare system is characterised by much stronger redistribution effects than the liberal UK one. Consequently, the relatively low-performing immigrant population in Germany profits more from the redistribution system than immigrants with similar socio-economic attributes in the UK.
Keywords: J15; J18; D31; 330; immigration; migration policy; income redistribution; Einwanderung; Ausländer; Ethnische Gruppe; Einkommensverteilung; Einkommensumverteilung; Vergleich; Großbritannien; Deutschland